Parenting Patterns and Their Implications for the Development of Early Childhood Social Attitudes - Rahimah, Rahimah; Sukiman, Sukiman (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2020)
This study aims to analyze parenting patterns and their impact on the development of early childhood social attitudes. This research is qualitative research using a case study design in class B Raudhatul Athfal (RA) Al-Is Syah Hakim Medan, on Jl. Karya Jaya, North Sumatra. This study's primary informants are the parents of students who carry out their family environment care. Data collection techniques were using observation, interviews, and documentation. Data analysis was through stages developed by Miles and Huberman. Checking the validity of the user data was through the triangulation of sources and techniques. This study indicated that the parenting patterns of early childhood parents of Class B RA Al-Is Syah Hakim Medan consist of three styles, i.e., permissive, authoritarian, and democratic parenting. The most dominant style of parenting parents as permissive parenting. Permissive parenting pattern has implications for the tendency of children to have poor social attitudes. Authoritarian parenting pattern has consequences for the tendency of children to have anti-social attitudes. The style of democratic parenting has implications for the tendency of children to have prosocial attitudes.